Factor Mobility, Regional Development, and the Distribution of Income - McCulloch, Rachel; Yellen, Janet L. (Journal of Political Economy, 1977)
A three-factor model of a small country or region is used to analyze the general equilibrium consequences of three frequently advocated regional development policies–investment subsidies, migration incentives, and educational expenditures. The analysis focuses on policy-induced changes in absolute and relative factor earnings. The results link changes in the distribution of income to the degree of complementarity and substitutability among factors of production and to the pricing scheme adopted by educational institutions. Programs intended to aid lagging regions may produce perverse results, particularly if the cost of education is the same to all individuals regardless of ability.